Culturally responsive and sustaining education : framing diversity, equity, and social justice education in a local to global context - White, Cameron (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"The book suggests that culturally responsive and sustaining education should be the guiding principle in our schools, and that community partnerships be developed in a similar light. Although many of the chapters focus on specific content or places, a transdisciplinary problem and project-based experiential critical pedagogy is an ultimate goal. This necessitates developing awareness, advocacy and action / engagement regarding issues of race, ethnicity, gender, ability, choice, and culture to promote equity and social justice. The stories included in this collection are those of educators in a variety of contexts, but always through a public education framing. The stories come from educators at all levels of public education who are currently practicing in one of the most diverse urban areas of the U.S. Their experiences serve to provide hope for transformational change in education where the priority is truly equity and social justice for all. The idea is to provide voices of these brave educators who are striving to address equity and social justice issues is schools, education, and society - on their teaching and in the students' learning"--